Prevalence and control of hypertension in COVID-19 positive cases - Mohamed O. Elamin; Sufian Khalid; Amjed A. Ali; Sara O. Elamin; Wahaj A. Khan; Hatim M. Badri; Hatim A. Natto; Abdulrahman A. Almehmadi; Abdullah Alhazmi; Ahmed Alkathiri; Mohamed Alharbi (Journal of Family Medicine and Primary Care)
Background: The coronavirus disease (COVID-19) is an infectious disease caused by the newly discovered SARS-CoV-2 virus. Patients diagnosed with COVID-19 experience several complications including hypertension or elevated blood pressure which is a serious medical condition that significantly increases the risks of heart, brain, and kidney diseases. Objectives: To assess the prevalence and control of hypertension in COVID-19 patients. Methods: Cross-sectional descriptive hospital-based study conducted in an isolation center at Atbara Teaching Hospital in 2021. The data were collected by interviewing patients through a close-ended questionnaire and analyzed using a statistical computerized program (SPSS version 21). Results: The main results of the study revealed that the prevalence of blood pressure amongst patients diagnosed with COVID-19 was mild 45%, moderate 17.7%, and severe 10%; of the cases, 25.7% were newly discovered hypertension cases, of the cases 26.7% were diabetic patients; and 70.7% of the study group full recovered form COVID-19 at discharge. Conclusion: The study concluded that most of the study group had hypertension with COVID-19, some of them were newly discovered cases of hypertension and also had diabetes mellitus which indicates that COVID-19 may cause the onset of hypertension.